2023
DOI: 10.3847/2041-8213/acba16
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosynthesis in Outflows from Black Hole–Neutron Star Merger Disks with Full GR(ν)RMHD

Abstract: Along with binary neutron star mergers, the inspiral and merger of a black hole and a neutron star is a predicted site of r-process nucleosynthesis and associated kilonovae. For the right mass ratio, very large amounts of neutron-rich material (relative to the dynamical ejecta) may become unbound from the post-merger accretion disk. We simulate a suite of four post-merger disks with three-dimensional general-relativistic magnetohydrodynamics with time-dependent Monte Carlo neutrino transport. We find that with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Further multi-messenger observations of BNS mergers will greatly improve the study conducted here. Moreover, we anticipate other developments that will enable more accurate modeling of BNS mergers and the composition of their ejecta, including advances in astrophysical simulations (e.g., Curtis et al 2023;Foucart et al 2023;Zappa et al 2023), nuclear experiments that will probe the physics of dense matter (Sorensen et al 2023) and the properties of increasingly exotic nuclei (e.g., Crawford et al 2022;Orford et al 2022), and improvements to the theoretical treatment of microphysics such as neutrino emission, absorption, and oscillations (e.g., Gizzi et al 2021;Balantekin et al 2023;Grohs et al 2023). Current and future surveys such as LSST, Roman, Zwicky Transient Facility, and ATLAS will enable greater studies of these rare phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Further multi-messenger observations of BNS mergers will greatly improve the study conducted here. Moreover, we anticipate other developments that will enable more accurate modeling of BNS mergers and the composition of their ejecta, including advances in astrophysical simulations (e.g., Curtis et al 2023;Foucart et al 2023;Zappa et al 2023), nuclear experiments that will probe the physics of dense matter (Sorensen et al 2023) and the properties of increasingly exotic nuclei (e.g., Crawford et al 2022;Orford et al 2022), and improvements to the theoretical treatment of microphysics such as neutrino emission, absorption, and oscillations (e.g., Gizzi et al 2021;Balantekin et al 2023;Grohs et al 2023). Current and future surveys such as LSST, Roman, Zwicky Transient Facility, and ATLAS will enable greater studies of these rare phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies of the physics behind these light curves have demonstrated the difficulties in determining the exact yields from the existing observations (Tanaka et al 2018(Tanaka et al , 2020Wollaeger et al 2018Wollaeger et al , 2021Even et al 2020;Fontes et al 2020; Barnes et al 2021). Simulations of the ejecta both during the merger and the subsequent accretion disk argue that the r-process can be produced throughout the merger (Miller et al 2019b;Curtis et al 2023;Kullmann et al 2023), but the mass and composition of this ejecta remains uncertain. These uncertainties must be characterized to use existing and future observations to determine the r-process yields from neutron star mergers and determine their role in r-process production in the Galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…In neutron star mergers, disk ejecta may be accompanied by dynamical ejecta (Dietrich & Ujevic 2017;Radice et al 2018) that is also sensitive to neutrino physics (Foucart et al 2023). Accretion disks from the merger of a neutron star-black hole binary are also found to be favorable sites of the r-process (Siegel & Metzger 2017;De & Siegel 2021;Murguia-Berthier et al 2021;Curtis et al 2023).…”
Section: Introductionmentioning
confidence: 99%